Research Results Boardify A Comprehensive Approach to Academic Task Management with Push Notifications and Scheduling Optimization - Faiz Syukri Arta Faiz; Muhammad FIkry; Rini meiyanti (LPPM Universitas Malikussaleh, 2024)
Abstract. This study explores the development and implementation of Boardify, an integrated academic task management system designed to enhance the thesis submission process for Informatics students. The system incorporates features such as task management, status tracking, file submission, and seamless communication between students and supervisors, aiming to streamline the entire workflow. By leveraging Firebase Cloud Messaging, Boardify enables real-time push notifications, ensuring timely updates and reducing delays. Furthermore, the implementation of scheduling algorithms optimizes notification timing based on probabilistic factors, enhancing the efficiency of the system. A comparative analysis was conducted between Boardify and similar task management platforms, focusing on aspects such as website load speed, feature functionality, and user experience. The system's performance was further evaluated by measuring the average time taken by supervisors to review student submissions. Results indicate that Boardify significantly improves the efficiency of the thesis submission process, enhancing transparency and facilitating effective communication. The findings underscore Boardify's potential as a powerful tool for academic institutions, offering a promising approach to optimizing educational task management and promoting the advancement of educational technology. Keywords: Boardify. Probability Scheduling, Push Notifications, Informatic, Task Management System